BREAST RECONSTRUCTION WITH PEDICLED TRANSVERSE RECTUS ABDOMINIS MUSCULOCUTANEOUS (TRAM) FLAP: RESULTS OF 10 YEARS EXPERIENCE - Müjdat Balkan; Semih Görgülü; Erkan Öztürk; Fatih Zor; İsmail Arslan; Mustafa Şengezer; Turgut Tufan (European Journal of Breast Health, 2008)

(untitled)
Breast-conserving surgery has become the standart strategy in breast cancer. At the same time immediate breast reconstruction is a popular method in the treatment of breast cancer. The autologous tissue reconstruction provides better cosmesis than silicone implants with acceptable complication rates. Immediate breast reconstruction with pedicled transverse rectus abdominis musculocutaneous (TRAM) fl ap following modifi ed radical mastectomy was attempted in 32 breast cancer patients in Gulhane Military Medical Academy General Surgery and Plastic and Reconstructive Surgery Departments between 1997 and 2006. Histological analysis showed invasive ductal carcinoma in 23 patients, invasive lobular carcinoma in 6 cases, mixed invasive carcinoma in 2 patient, and squamous cell cancer in 1 patient. Local fl ap necrosis, abdominal hernia and donor site bursa were seen in 1 patient in early postoperative period while minimal fl ap necrosis was detected in 1 patient in late postoperative period. We did not see any complications in the rest of the patients. There was no observed local or systemic recurrence during the follow-up period (mean, 60 months). We concluded that immediate breast reconstruction is a safe and eff ective procedure with very good cosmetic results and it provides an improvement in social life of patients.